DETERMINATION OF THE DYNAMICS OF THE FORMATION OF WOOD RESIDUES AND WASTE FROM PRODUCTION ACTIVITIES AT LLC "FORTUNA-MEBLI" - Kyyanka, Volodymyr; Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2024)
A comparative analysis of the dynamics of the formation of residues and waste from the processing of wood and composite structural materials into blanks at the furniture enterprise LLC "Fortuna-mebli" for three years (2022-2024) was performed. The dynamics of the volume of accumulation of waste and residues from the processing of beech wood and structural materials: MDF boards, chipboard and plywood was analyzed in detail. It was established that during the three-year period, a stable decrease in the total amount of waste and residues at the enterprise was observed at this enterprise, which indicates successful measures to optimize production processes. The total amount of waste and residues at the enterprise showed a decrease from 54.80 m³ in 2022 to 30.48 m³ in 2024, which indicates an overall improvement in the efficiency of waste management and optimization of production processes during the analyzed period. It was found that the amount of solid residues - scraps decreased from 35.23 m³ in 2022 to 19.58 m³ in 2024. A slight decrease in 2023 (by 3%) may be due to minor improvements in processing processes, while a significant decrease in 2024 ( 43%) indicates a significant improvement in processing methods and material use. A decrease in sawdust and shavings was determined. Sawdust waste initially experienced a small increase from 11.92 m³ in 2022 to 12.58 m³ in 2023 ( 6% increase), after which it decreased significantly to 6.65 m³ in 2024 ( 47% decrease), which is the result of optimization of cutting processes. The amount of shavings waste decreased from 7.65 m³ in 2022 to 4.24 m³ in 2024. A decrease of 38% from 2022 to 2023 and a further moderate decrease ( 10%) from 2023 to 2024 indicate effective management of this type of waste and the possibility of its reuse. It is substantiated that reducing waste volumes contributes to reducing the costs of its disposal, improving the environmental image of the enterprise and increasing its competitiveness in the market.